Validity of Holland’s Model: A Confirmatory Factor Analysis - Khan, Sar B; Alvi, Sabir A.; Kirkwood, Kristian J. (Canadian Journal of Counselling and Psychotherapy, 2011)
Confirmatory factor analysis was used to investigate the validity of Holland's model for a sample of 155 Canadian high school students. The analysis revealed that Holland's model was quite appropriate in explaining the relationships among six personality types: Realistic, Investigative, Artistic, Social, Enterprising and Conventional across the areas of Activities, Competencies, Occupations and Self-Estimates in the Self-Directed Search.